HUBUNGAN SELF EFFICACY DAN DUKUNGAN KELUARGA DENGAN SELF CARE PADA PASIEN DIABETES MELITUS TIPE II DI UPTD PUSKESMAS KADUDAMPIT KABUPATEN SUKABUMI - Suci, Suci Fitriyani Amanda Kartini; Dewi, Rosliana; Liawati, Nunung (Jurnal Mutiara Kesehatan Masyarakat, 2023)
Diabetes mellitus is a metabolic illness which is a world issue. The occurrence rate will increment until 2045. This study expects to break down the connection among family support and self-efficacy with self-care of oneself on the patient with DM. The examination configuration utilized quantitative exploration with a cross sectional review. The populace in this research is all DM patients  visited in puskesmas for quite some time, to be specific 51 patients and the example in this study were all populaces. The most effective method to take tests in this review utilizing unintentional examining. The information investigation utilized was bivariate and univariate examination with Chi-Square. The outcomes show that most of self-efficacy is high, family support is strong, and self care of oneself is great. In light of the consequences of the connection test, it was acquired that the huge worth of the connection among self-efficacy and self care of oneself was sig = 0.010, family support with taking care of oneself was sig = 0.005. The end in this examination is that there’s a connection among self-efficacy and family support with self care of oneself in Type II DM  patients at the UPTD Puskesmas Kadudamit, Sukabumi Regency.